Efeitos da administração profilática pós-eclosão de ceftiofur e da suplementação com sanguinarina na microbiota cecal de pintinhos - Lemos, Mateus Lacerda Pereira (2020)
The prophylactic application of ceftiofur to newly hatched broiler chickens is a common practice in several hatcheries. We investigated the effects of this practice on the cecal microbiota of 14 days-old chicks. Furthermore, we also investigated the effects of the dietary supplementation of sanguinarine on the gut microbiota. DNA samples were extracted from cecal contents, amplified for thev3-v4 regions of the microbial 16S rRNA gene and sequenced in an Illumina Miseq platform. After downstream bioinformatics and statistical analyses, our results demonstrated that both treatments involving ceftiofur and sanguinarine treatments increased the proportions of the phylum Bacteroidetes, and the genus Bacteroides and Megamonas in the cecum of birds while reduced the relative abundance of the Firmicutes phylum and the Lachnospiraceae family. The functional prediction indicated an increase in metabolic pathways associated with digestibility in the microbiota of birds treated with ceftiofur. Diversity and abundance changes in the cecal bacterial community of broiler chickens triggered by ceftiofur were similar to those observed in the birds receiving sanguinarine-supplemented diet. Such findings support previous reports on the productivity benefits of sanguinarine as an alternative compound to improve gut health.